Convective Environments Within Mediterranean Cyclones - Alice Portal; Andrea Angelidou; Raphael Rousseau‐Rizzi; Shira Raveh‐Rubin; Yonatan Givon; Jennifer L. Catto; Francesco Battaglioli; Mateusz Taszarek; Emmanouil Flaounas; Olivia Martius (Atmospheric Science Letters)
ABSTRACT Mediterranean cyclones can trigger severe weather hazards, including convective precipitation, lightning and hail, with implications for operational forecasting, risk assessment in the insurance industry, and societal preparedness. This work examines the climatological link between Mediterranean cyclones and atmospheric conditions conducive to severe convection. Using ATDnet lightning detections we find that, from autumn to spring, 20%–80% of lightning hours over the Mediterranean basin and adjacent land regions are associated with nearby cyclones. Based on reanalysis data, we demonstrate that severe convective environments and associated hazards predominantly occur in the warm sector of Mediterranean cyclones and to the north‐east of their centres. Convective processes and hazards exhibit a peak approximately 6 h prior to the time of minimum pressure of the cyclone centre, consistent with previous studies. Additionally, we find a strong seasonal dependence of severe convection within cyclones. Severe convective environments are often detected in cyclone types typical of transition seasons (autumn especially) and summer, while they are rarer in deep baroclinic cyclones characteristic of winter. Finally, we provide novel insights regarding the dependence of convective activity on the presence of dynamical features around Mediterranean cyclones. Warm conveyor belts, characterised by large‐scale ascent and high thermodynamic instability, emerge as the most favourable regions for lightning activity, with lightning potential being twice as high compared to cyclone cold fronts. These results advance our understanding of the interplay between cyclone dynamics and severe convection, offering valuable guidance for improving hazard prediction and for elaborating weather emergency strategies in the Mediterranean region.